SPIRITUAL EMPLOYER BRANDING AND TURNOVER INTENTION: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT IN AN FAITH-BASED INSTITUTION - Nur Aqilah Rahmayati; Sari Laelatul Qodriah; Harry Safari Margapradja (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the effect of employer branding on turnover intention in Islamic boarding schools (pesantren) in Cirebon Regency, with organizational commitment serving as a mediating variable. A quantitative research design was employed, with 73 respondents selected through proportional sampling from a population of 275 employees. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software to assess the relationships among variables. The findings indicate that employer branding has a significant negative effect on turnover intention. Furthermore, organizational commitment significantly mediates the relationship between employer branding and turnover intention. These results suggest that strengthening employer branding can effectively reduce employees’ intention to leave, particularly when it fosters higher levels of organizational commitment. This study contributes to the literature on employee retention in faith-based educational institutions. However, as the research is limited to pesantren within a single district, the generalizability of the findings remains constrained. Future research is encouraged to incorporate additional determinants of turnover intention to provide a more comprehensive understanding of retention strategies in religious-based organizations. Keywords: Employer Branding; Organizational Commitment; Turnover Intention